Efisiensi Boiler dan Turbin Uap Untuk PLTU Unit 2 PT. XYZ - Mubarak, Husni; Mahmuddin, Mahmuddin; Sungkono, Sungkono; Arham, Muhammad (Universitas Nusantara PGRI Kediri, 2024)
PT. XYZ has an electric power capacity of 70 MW and began operating in 2014 during its operation there has been a decrease in power from 35 MW at the time of commissioning to 32 MW. This study investigates the impact of the air-fuel ratio (AFR) on the efficiency of a thermal system, focusing on the boiler, turbine, and overall thermal cycle efficiency. Variations in excess O2 in flue gas were examined at levels of 5.0%, 5.5%, and 6.0%. The results reveal that the boiler efficiency peaks at 5.0% excess O2 (73.50%), while an increase in excess O2 or AFR leads to a decrease in efficiency. Turbine efficiency remains relatively stable (74-76%) despite a slight decline with increased AFR. The thermal cycle efficiency reaches its maximum at an AFR of 13.61 (45.60%) but diminishes at higher AFR values.